Parliamentary interpellations in educational research - Sánchez-Claros, Juan Patricio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper looks at parliamentary interpellations as educational research material. After considering the legislation and the control function in this field, the appropriate discourse analysis modalities for their treatment are discussed. This is followed by a quantitative breakdown of the interpellations registered in the database of the Congress of Deputies throught the different democratic legislatures, indicating their content. Finally, three of them are selected to which a content analysis based on the discursive approach described below is applied.